2014
DOI: 10.1108/ict-02-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Green training supporting eco-innovation in three Brazilian companies: practices and levels of integration

Abstract: Purpose – The purpose of this paper is to show results from the relationship between green/environmental training and the development of three projects of low-carbon eco-innovations in top Brazilian companies. Design/methodology/approach – This study includes three organizational projects for low-carbon eco-innovations in products (A, B and C) with the objective of reducing their impact on GHG emissions, the so-called low-carbon products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…This calls for HRM education to aim at empowering students to address sustainability concerns of their stakeholders (Van Buren and Greenwood, 2013). Accordingly, our findings reinforce calls by Piwowar-Sulej (2021), Saturnino Neto et al (2014) and Van Buren and Greenwood (2013) for HRM policymakers and training institutions to emphasise more sustainability in HRM courses and programmes. Aside, our study provides organised and rich information that can be used in teaching students about the context of sustainable HRM implementation and related issues.…”
Section: Implications and Conclusionsupporting
confidence: 83%
“…This calls for HRM education to aim at empowering students to address sustainability concerns of their stakeholders (Van Buren and Greenwood, 2013). Accordingly, our findings reinforce calls by Piwowar-Sulej (2021), Saturnino Neto et al (2014) and Van Buren and Greenwood (2013) for HRM policymakers and training institutions to emphasise more sustainability in HRM courses and programmes. Aside, our study provides organised and rich information that can be used in teaching students about the context of sustainable HRM implementation and related issues.…”
Section: Implications and Conclusionsupporting
confidence: 83%
“…Environmental-training is reported as one of the most crucial aspects of human resource practices (Jabbour et al , 2013). In a study conducted in Brazil, it was reported, “environmental-training for mitigating climate change” is relevant for the systematic development of low-carbon products (Saturnino Neto et al , 2014). Further, both direct and moderating effects of employee training were found on the organization’s sustainable development (Ji et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational eco-innovations help reduce the information deficits regarding the detection of potential cost savings, mainly in materials and energy (Porter & Van der Linde, 1995;Horbach, 2008). In addition, they contribute to higher success in the development of eco-innovative or low-carbon products (Neto, Jabbour & Jabbour, 2014), once product impact analysis will inevitably involve several functional areas in life Environmental Management and Sustainable Development ISSN 2164-7682 2020 cycle assessment (LCA) (Pujari, Wright & Peattie, 2003). Cheng et al (2014), Neto et al (2014) and Brasil et al (2016) suggest that organizational eco-innovations play a fundamental role in enhancing product eco-innovations, by favoring environmental protection and the adoption of clean and eco-efficient technologies.…”
Section: Relations Between Organizational and Technological Eco-innovmentioning
confidence: 99%
“…In addition, they contribute to higher success in the development of eco-innovative or low-carbon products (Neto, Jabbour & Jabbour, 2014), once product impact analysis will inevitably involve several functional areas in life Environmental Management and Sustainable Development ISSN 2164-7682 2020 cycle assessment (LCA) (Pujari, Wright & Peattie, 2003). Cheng et al (2014), Neto et al (2014) and Brasil et al (2016) suggest that organizational eco-innovations play a fundamental role in enhancing product eco-innovations, by favoring environmental protection and the adoption of clean and eco-efficient technologies. However, previous empirical studies, as Garcí a-Granero et al 2020did not test the association between organizational and product eco-innovation.…”
Section: Relations Between Organizational and Technological Eco-innovmentioning
confidence: 99%